Mitigating Broadcast Storm on Metro Ethernet Network Using PVST+ - Beny Nugraha; Bayu Fitrianto; Fahraini Bacharuddin (Universitas Ahmad Dahlan, 2016)
Broadcast storm attack on the layer 2 networks included looping and duplicate packets that are transmitted continuously in order to prevent the service of the network, thus, it is the type of attack that is against availability. In this research, a Spanning Tree Protocol method, namely PVST+ (Per VLAN Spanning Tree Plus), is used to overcome the problem caused by the broadcast storm attack on Metro Ethernet Network. The PVST+ serves as a redundant network management and it prevented looping on the network. The result obtained from this research is PVST+ is able to mitigate broadcast strom that is shown by the decrease of number of packets and the decrease of the average packet per-second. The average packets per-second on VLAN 1 decrease to 274,041 and the average packets on VLAN 10 decrease to 267,794 packets per-second.